Optimization of a divided wall column for the separation of C4-C6 normal paraffin mixture using Box-Behnken design - Sangal Vikas K.; Kumar Vineet; Mishra Mani Indra (Chemical Industry and Chemical Engineering Quarterly, 2013)
In the present study, simulation of a divided wall column (DWC) was carried out to study the product quality and energy efficiency as a function of reflux rate, liquid spilt and vapour split for the separation of C4-C6 normal paraffin ternary mixture. Rigorous simulation of the DWC was carried out using Multifrac model of ASPEN Plus software. Box-Behnken design (BBD) was used for the optimization of parameters and to evaluate the effects and interaction of the process parameters such as reflux rate (r), liquid split (l) and vapour split (v). It was found that the number of simulation runs reduced significantly for the optimization of DWC by BBD. Optimization by BBD under response surface methodology (RSM) vividly underscores interactions between variables and their effects. The predictions agree well with the results of the rigorous simulation.